Development of the target orientation of the personality of adolescent tourists - Onуschenko Vitalyi (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article is devoted to the problem of personality target orientation , as one of the central component of the personality-motivational development of the teenager, in the context of sports and tourism activity. The research is based on the assumption that accelerating the development of the target orientation of the individual in adolescents is possible by activating its components in the conditions of tourism activity. Present article provides the study model of the tennagers personality targeting. The article presents the results of the study of the development of the target orientation of the personality of teenagers-tourists, supported by qualitative and quantitative research methods, in particular, the content structure of adolescent personality orientation and a number of key factors influencing orientation in these areas were analyzed. The research is based on the assumption that accelerating the development of the target orientation of the individual in adolescents is possible by activating its components in the conditions of tourism activity. It is statistically determined that the leading target areas of adolescent tourists are the individualistic and self-activity areas of interest; Friendly, family, and educational focuses are moderate, while the social and intimate target areas are the least prioritized. In addition, the study of the personal position showed that among adolescents prevails self-centered position, the second largest is the rational position, the least common – the altruistic position. It is found, that interaction in a group during competitions and trips promotes the development of teamwork and a comfortable microclimate that affects the emotional sphere of adolescents. The use of cards of the indicative basis of action at the training is cognitive activity, the growth of motivation to study, as well as the development of rational and altruistic positions of the target orientation of the personality of adolescents, thus contributing to the personnel development and subjective well-being. Situation of the test, that create personal challenge to teenager, during training and competitions, complex route sections and adverse weather conditions in the campaign cause adaptive correction of the condominium component. The system of job vacancies, tourist regulations and values contribute to the development of the value component of the target orientation of adolescents.